The writing of Mina Loy between the feminine figurations in the late 19th century - Pugliesi, Lucas Bento (Revista Criação & Crítica, 2017)
This papper will deal with the ambivalence of Mina Loy's thought as presented on her poems and on the Feminist Manifesto, understanding it as a response to European psychology from the turn of the nineteenth century to the twentieth century, especially the conceptions of the feminine by Otto Weininger. In this way, it is intended to understand how a poetic form already carries in itself something of an invective against the masculine way (DERRIDA, 1993) to value the knowledge, which Loy intends to destroy in favor of positive affirmations of a feminine identity.